RURAL YOUTH: WORK AND SPACE MOBILITIES IN AN HORTICULTURAL REGION IN ARGENTINA - Marioni, Lucía (2019)
This paper presents rural youth`s practices and representations about their work and space mobilities in small producers families in Argentina. From an ethnographic methodology, the research was made from june 2016 to june 2017. The main contributions refers to invisibilization and gender inequalities at work and characterization of the daily spatial mobility between that they identify as antagonistic spaces: “the countryside” and “the city”.